2016
DOI: 10.1371/journal.pone.0153792
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Differences of Vocal Tract Articulators in Different Loudness Conditions in Singing

Abstract: IntroductionDynamic MRI analysis of phonation has gathered interest in voice and speech physiology. However, there are limited data addressing the extent to which articulation is dependent on loudness.Material and Methods12 professional singer subjects of different voice classifications were analysed concerning the vocal tract profiles recorded with dynamic real-time MRI with 25fps in different pitch and loudness conditions. The subjects were asked to sing ascending scales on the vowel /a/ in three loudness co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 51 publications
0
21
0
5
Order By: Relevance
“…Previous research has shown that untrained subjects tend to elevate the larynx when pitch is raised [56, 57]. For trained singers, both laryngeal lowering [58] and raising [11, 59] have been observed relative to increased pitch. When loudness is increased, the larynx has been shown to lower in trained singers [59, 60].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that untrained subjects tend to elevate the larynx when pitch is raised [56, 57]. For trained singers, both laryngeal lowering [58] and raising [11, 59] have been observed relative to increased pitch. When loudness is increased, the larynx has been shown to lower in trained singers [59, 60].…”
Section: Discussionmentioning
confidence: 99%
“…B: Mid-sagittal MRI slice through the human brain and skull. Real-time MRI permits the observation of articulator movements during song and speech [105]. Structural image from M. Echternach, M. Burdumi, L. Traser, B. Richter, Universitätsklinikum Freiburg, Germany (https://www.youtube.com/watch?v=GCluRCd2YuM)…”
Section: Figurementioning
confidence: 99%
“…A detailed description of these factors is beyond the scope of this paper; however, as a starting point, the reader is directed to Johan Sundberg's chapter in The Psychology of Music (Sundberg, 2013). Generally, these factors may be described as (a) variations across pitch and loudness (Echternach et al, 2016), (b) variations based on singing style (Sundberg et al, 1993Thalén and Sundberg, 2001;Stone et al, 2003;Björkner, 2008;Borch and Sundberg, 2011;Bourne and Garnier, 2012;Guzman et al, 2015;Sundberg and Thalén, 2015;Yang et al, 2015;Bourne et al, 2016;Hallqvist et al, 2017), (c) variations based on vocal register (Titze, 1994;Sundberg and Kullberg, 1999;Sundberg and Högset, 2001;Roubeau et al, 2009), and (d) variations based on the need for a singer's formant cluster (Sundberg, 1974(Sundberg, , 1994(Sundberg, , 2001(Sundberg, , 2013Dmitriev and Kiselev, 1979;Bloothooft and Plomp, 1986;Barnes et al, 2004;Johnson and Kempster, 2011;Mainka et al, 2015;Story, 2016). Thus, while speakers may keep a relatively constant glottal excitation source spectral slope and exhibit relatively small variations in VTL during speech, successful professional singers must learn to purposefully modify both the glottal excitation source and the vocal tract filter, resulting in vocal productions that are physiologically, acoustically, and perceptually much different from those of speech in many cases.…”
Section: Introductionmentioning
confidence: 99%